IRRIGATIONAL THERAPY IN PEDIATRIC RHYNOLOGY - E.P. Karpova; E.E. Vagina (Вопросы современной педиатрии, 2009)
The article describes main problems related to the development of rhinitis in newborns and infants. Authors consider the advantages of irrigational therapy in children under this age for the purpose of nasal breathing recover and prophylaxis of diseases of nose and nasopharinx. The stages of its fulfillment, the medications, optimal for the daily hygiene of nasal cavity are described.Key words: newborns, infants, rhinitis, hygiene of nasal cavity, irrigational therapy.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(5):115-118)